2022
DOI: 10.1186/s12933-021-01439-8
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin-A and risk of diabetes-related vascular complications: a prospective study

Abstract: Background Fetuin-A is a hepatokine which has the capacity to prevent vascular calcification. Moreover, it is linked to the induction of metabolic dysfunction, insulin resistance and associated with increased risk of diabetes. It has not been clarified whether fetuin-A associates with risk of vascular, specifically microvascular, complications in patients with diabetes. We aimed to investigate whether pre-diagnostic plasma fetuin-A is associated with risk of complications once diabetes develops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
(65 reference statements)
4
8
0
Order By: Relevance
“…It has been shown that high levels of FETU-A can be considered a risk factor for insulin resistance, T2DM, CVD by inhibition of adiponectin expression, peroxisome proliferator-activated receptor-γ (PPARγ) or activating the toll-like receptor 4 (TLR-4), and as a factor reducing the risk of coronary artery disease [ 41 ]. The level of FETU-A, as a negative acute phase protein, decreases in the course of inflammation and increases again after recovery [ 41 ]. FETU-A may therefore be useful in monitoring inflammation in HIV patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that high levels of FETU-A can be considered a risk factor for insulin resistance, T2DM, CVD by inhibition of adiponectin expression, peroxisome proliferator-activated receptor-γ (PPARγ) or activating the toll-like receptor 4 (TLR-4), and as a factor reducing the risk of coronary artery disease [ 41 ]. The level of FETU-A, as a negative acute phase protein, decreases in the course of inflammation and increases again after recovery [ 41 ]. FETU-A may therefore be useful in monitoring inflammation in HIV patients.…”
Section: Discussionmentioning
confidence: 99%
“…A lower fetuin-A concentration is associated with greater risk of microvascular and macrovascular complications in T2DM patients. 71 Interestingly, individuals with T2DM and NAFLD often present with a cardiac autonomic nervous system imbalance, displaying an increase in sympathetic tone, 72 , 73 which is associated with increased blood pressure and risk of ventricular arrythmia in T2DM. 74–76 …”
Section: Current Understanding Of the Mechanisms Underlying Diabetic ...mentioning
confidence: 99%
“…An interesting hepatokine with regards to IR is fetuin-A [ 127 , 128 , 129 , 130 ]. Fetuin-A is also linked to diabetes microvascular complications [ 131 ] and the development of nonalcoholic fatty liver disease (NAFLD) [ 132 ]. Saturated fatty acids may induce IR either by providing substrate for ceramide biosynthesis [ 133 ], or by activating toll-like receptor 4 (TLR4) signaling [ 123 ].…”
Section: Effects Of Long-term Pa On Irmentioning
confidence: 99%